PENINGKATAN KETERAMPILAN PEMBUATAN TEPUNG PISANG DAN BROWNIES PISANG PADA KELOMPOK PEREMPUAN PRODUKTIF DI DESA SENGKUBANG KABUPATEN MEMPAWAH: Improvement of Banana Flour and Banana Brownies Making Skills in Productive Women Group in Sengkubang Village, Mempawah District - Rikhsan Kurniatuhadi; Kustiati; Siti Ifadatin; Siti Khotimah; Ari Hepi Ari Hepi Yanti; Tri Rima Setyawati; Firman Saputra; Dwi Gusmalawati; Riza Linda; Rafdinal; Elvi Rusmiyanto PW; Riyandi (JAMAS : Jurnal Abdi Masyarakat, 2023)
Sengkubang Village is a mangrove area located in Mempawah Hilir District, Mempawah Regency, West Kalimantan. Sengkubang Village already has a Coastal Community Group that cares about the preservation of mangroves. However, community empowerment still needs to cover women's communities. Most women in Sengkubang Village work as housewives or help their husbands with the gardens. The implementation of community service focuses on empowering the women of Sengkubang Village by providing skills based on natural wealth and plantation products around their residences. Through this skills training, it is hoped that women will be able to fill their spare time by producing banana flour and brownies made from banana flour which are of the sale value. The method of implementing PKM is through short skills training, and participants can bring home their work. The evaluation of PKM activities was carried out using the questionnaire method at the end of the training. The training results showed the enthusiasm of the women's group from the Pelesir community in making banana flour and brownies made from banana flour. 100% of participants strongly agreed that the theme and training could develop their potential to increase their income and daily activities. Subsequent developments will include product marketing assistance through social media and e-commerce.